Juridical Review of Medical Services at The Bhayangkara Hospital Sabara Education Center Porong - Zubaidah, Risna (Kirana Publisher (KNPub), 2024)
This study discusses the Juridical Review of Medical Services at the Bangil Regional General Hospital. The formulations in this study are (1) What is the legal relationship between doctors and patients in the action of medical services at the Bangil regional general hospital. (2) Is every doctor responsible for the patient in the efforts of medical services in the hospital. (3) what factors affect the implementation of medical services in hospitals. This study aims to determine: (1) how the legal relationship between doctors and patients in the act of medical services at the Bangil area general hospital. (2) Is every doctor responsible for the patient in the efforts of medical services in the hospital. (3) what factors influence the implementation of medical services at the Bangil Regional General Hospital. Based on the results of this study indicate that 1) The legal relationship that occurs between doctors and patients in medical service actions at the Bangil Regional General Hospital is when the patient states his complaint and is then responded to by the doctor and when the patient is examined by the doctor, where the doctor has stated willingness which is expressed verbally or implicitly in showing an attitude or action that concludes the doctor's willingness. 2) A doctor is always responsible for every action given to his patient.